REVIEW OF ETHICS ON TELEMEDICINE SERVICES IN INDONESIA: A LITERATURE REVIEW STUDY - Salsabila, Gladis; Hartono, Budiman; Salim, Darminto (Jurnal MedScientiae, 2024)
Telemedicine as an online consultation tool is also developing in Indonesia. in addition, Indonesia currently does not have a clear legal umbrella for telemedicine issues. This literature review aims to provide an overview of telemedicine services in Indonesia from an ethical perspective. Of the 7 studies reviewed by the authors, there are various expert opinions that differ from an ethical perspective regarding telemedicine, so that it can be concluded that telemedicine can be used to provide health services, but priority must be given to the application of ethical and legal principles. Inappropriate use of telemedicine will cause problems for the patient and the doctor himself. Problems that can occur such as the problem of demands given by patients to doctors in this case malpractice. Respect for ethical and legal principles must always be obeyed by every doctor because it saves doctors from lawsuits and demands while at the same time reflecting the personality of the doctor as a noble and noble profession of all time. It is necessary to make regulations related to telemedicine services in the medical field and the need for further research related to the extent of the use of telemedicine in Indonesia.